Contribution of steel fiber in a small scale reinforced concrete beam - Nonih, Gampuhur (2015)
Since today, fiber reinforced concrete is one of the most realistic materials to develop the use of concrete in load-bearing structure. The hooked-end steel fiber with two different the aspect ratio were used in this study. They are 65 mm aspect ratio with 0.55mm in diameter and 35 mm in length and 0.75 mm in diameter, 60 mm in length with 80 mm in aspect ratio. The volume fraction for both of steel fiber used is 1%. There are four concrete batches and each of batches consists of 3 beam specimens with dimension 750 mm x150 mm x150 mm and 6 cube specimens with 150 mm x 150 mm x 150 mm dimension. The beams were tested at 28 days under two-point load. The result showed that the addition of steel fiber in concrete improved the first cracking load, ultimate load, and ductility of the concrete beam. In comparison in terms of concrete compressive strength, SF35 improved for 12.94% and SF60 improved for 26.51% at 7days. Meanwhile, the compressive strength improved for 14.15% and 23.58% at 28 days for SF35 and SF60, respectively. The first crack (Pcr) was determined for the result obtained in experimental and SFRC showed significant increases to first crack load over conventional reinforced concrete beam. The SFRC beam with SF35 increased for 56.33% and SF60 for 68.67% for ultimate load (Pu), when compared to conventional reinforced concrete beam. This shows that longest SF was effective in resisting beam ultimate load compared with shortest SF.